Time-inconsistent preferences, consumption, investment and life insurance decisions. Issue 5 (11th March 2020) - Chen, Shou; Li, Guangbing
ABSTRACT: In this paper, we study a consumption, investment and life insurance strategy model in which agent has time-inconsistent preferences. We numerically find that time-inconsistent preferences lead agent to more consumption–wealth ratio and less insurance–wealth ratio, and that time-inconsistent agent purchases life insurance in advance. Moreover, both the consumption–wealth ratio and amount of life insurance purchased for naive agent are less than for sophisticated one, while total available wealth for naive agent is more than for sophisticated one. In particular, total amount of life insurance purchased increases when agent is young, but the situation reverses when she is older.